EFEKTIF PENGGUNAAN PODCAST TERHADAP PENDENGARAN DAN MOTIVASI BELAJAR SISWA - Niken Peby Pindarosa; Niken Peby Pindarosa (Universitas Muhammadiyah Muara Bungo, 2022)
Listening activities which are interactive processes need to be presented as interactive processes in learning to increase student motivation. This research was conducted to explore information about improving students' listening skills and interest in learning through the use of podcasts. Qualitative research methods were used in this research. Research on motivational teaching strategies that can improve students' listening skills. The strategy proposed here includes implementing Student Teams Achievement Division (STAD) using podcast media. Research shows that podcasts can not only improve students' listening skills but also increase their active participation in learning activities. Overall, this research shows that the development of English listening skills can be enhanced through podcasts.